Analysis of Chloroplast Genomes Provides Insights Into the Evolution of Agropyron - Han, Huijie; Qiu, Rui; Liu, Yefei; Zhou, Xinyue; Gao, Cuiping; Pang, Yongzhen; Zhao, Yan (Frontiers in Genetics, 2022)
Plants of the Agropyron genus are important pasture resources, and they also play important roles in the ecological restoration. Chloroplast genomes are inherited from maternal parents, and they are important for studying species taxonomy and evolution. In this study, we sequenced the complete chloroplast genomes of five typical species of the Agropyron genus (eg., A. cristatum × A. desertorum Fisch. Schult, A. desertorum, A. desertorum Fisch. Schult. cv. Nordan, A. michnoi Roshev, and A. mongolicum Keng) using the Illumina NovaSeq platform. We found that these five chloroplast genomes exhibit a typical quadripartite structure with a conserved genome arrangement and structure. Their chloroplast genomes contain the large single-copy regions (LSC, 79,613 bp-79,634 bp), the small single-copy regions (SSC, 12,760 bp-12,768 bp), and the inverted repeat regions (IR, 43,060 bp-43,090 bp). Each of the five chloroplast genomes contains 129 genes, including 38 tRNA genes, eight rRNA genes, and 83 protein-coding genes. Among them, the genes trnG-GCC, matK, petL, ccsA, and rpl32 showed significant nucleotide diversity in these five species, and they may be used as molecular markers in taxonomic studies. Phylogenetic analysis showed that A. mongolicum is closely related to A. michnoi, while others have a closer genetic relationship with the Triticum genus.